2021
DOI: 10.1186/s12886-021-01854-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between ambient temperature, particulate air pollution and emergency room visits for conjunctivitis

Abstract: Background Numerous studies have confirmed the association of ambient temperature and air pollution with a higher risk of morbidities, yet few have addressed their effect on the ocular system. The purpose of this study was to assess the association between temperature, air pollution, and emergency room visits for conjunctivitis. Methods In this case-crossover study, the records of all emergency room visits to Soroka University Medical Center (SUMC)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In a nationwide, population‐based, cross‐sectional study, Lee et al found that patients with allergic conjunctivitis had increased incidence in May (spring), September (autumn), and the valley in winter (Lee et al 2020 ). However, data from a case-crossover study between the years 2009 and 2014 conducted by Khalaila et al suggested that patients for conjunctivitis increased during summer and autumn, excluding spring and winter (Khalaila et al 2021 ). In addition, a study based on the population in Northeast China, between the years 2014 and 2018, showed that with the increase in temperature and the decrease in humidity, allergic conjunctivitis appears to increase significantly, indicating dry and hot climate is likely to induce allergic conjunctivitis (Lu et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a nationwide, population‐based, cross‐sectional study, Lee et al found that patients with allergic conjunctivitis had increased incidence in May (spring), September (autumn), and the valley in winter (Lee et al 2020 ). However, data from a case-crossover study between the years 2009 and 2014 conducted by Khalaila et al suggested that patients for conjunctivitis increased during summer and autumn, excluding spring and winter (Khalaila et al 2021 ). In addition, a study based on the population in Northeast China, between the years 2014 and 2018, showed that with the increase in temperature and the decrease in humidity, allergic conjunctivitis appears to increase significantly, indicating dry and hot climate is likely to induce allergic conjunctivitis (Lu et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from devastating systemic attacks on humans by adenovirus, it has gained great attention from ophthalmologists as a potential cause of an epidemic of conjunctivitis globally. Being more prevalent among all conjunctivitis, a significant rise in viral conjunctivitis had been observed, particularly in summers from July to August, while bacterial incidence was high in winter from December to April 1 . Matted eyelids due to purulent discharge and lack of itching in bacterial conjunctivitis are labeled as differentiating symptoms from viral conjunctivitis 2 .…”
mentioning
confidence: 99%